Identification and Characterization of the DMRT11E Gene in the Oriental River Prawn Macrobrachium nipponense - Wang, Yabing (Int J Mol Sci, 2019)
The doublesex and mab-3 related transcription factor (DMRT) gene family involvement in sex development is widely conserved from invertebrates to humans. In this study, we identified a DM (Doublesex/Mab-3)-domain gene in Macrobrachium nipponense, which we named MniDMRT11E because it has many similarities to and phylogenetically close relationships with the arthropod DMRT11E. Amino acid alignments and structural prediction uncovered conservation and putative active sites of the DM domain. Real-time PCR analysis showed that the MniDMRT11E was highly expressed in the ovary and testis in both males and females. Cellular localization analysis showed that DMRT11E was mainly located in the oocytes of the ovary and the spermatocyte of the testis. During embryogenesis, the expression level of MniDMRT11E was higher at the cleavage stage than at other stages. During the different stages of ovarian development, MniDMRT11E expression gradually increased from OI to OIII and decreased to the lowest level at the end of OIV. The results indicated that MniDMRT11E probably played important roles in embryonic development and sex maturity in M. nipponense. MniDMRT11E dsRNA injection also significantly reduced vitellogenin (VG) expression and significantly increased insulin-like androgenic gland factor (IAG) expression, indicating a close relationship in gonad development.